2022
DOI: 10.1021/acs.jnatprod.1c00900
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Dimeric Benzophenones from an Endophytic Pleosporales Species

Abstract: Eight new polyketides, including three dimeric benzophenones, named dipleosporones A−C (1−3), three benzophenones (4−6), one xanthone (7), and one phenylbenzoate (8), along with seven known polyketides (9−15) were isolated from the fungus Pleosporales sp. YY-4. The structures of the new compounds were established on the basis of spectroscopic methods, including high-resolution electrospray ionization mass spectrometry and one-and two-dimensional nuclear magnetic resonance. This is the first report of a benzoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Considering that previous studies have reported the anti‐inflammatory activity of the extracts of Paraconiothyrium sp., [23] and the anti‐inflammatory activity can be measured by determining the inhibition rate of NO production in a LPS‐induced model [24] . In the current study, the anti‐inflammatory activity of all the isolates were evaluated in LPS‐treated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that previous studies have reported the anti‐inflammatory activity of the extracts of Paraconiothyrium sp., [23] and the anti‐inflammatory activity can be measured by determining the inhibition rate of NO production in a LPS‐induced model [24] . In the current study, the anti‐inflammatory activity of all the isolates were evaluated in LPS‐treated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The cell counting kit-8 (CCK-8) (Dojindo, Japan) assay was used to evaluate the cell viability. [24] The RAW 264.7 cells were cultured in Dulbecco's Modified Eagle Medium (DMEM, Gibco) supplemented with 10 % fetal bovine serum (FBS, Gibco) and 1 % penicillinstreptomycin solution for 24 h. The RAW 264.7 cells (8 × 10 3 cells/ well) were cultured in 96-well plates for 24 h, 100 μM of compounds 1-5 were then added to the wells. The cells were incubated at 37 °C for another 24 h. Then 10 μL of the CCK-8 solution was added to each well and the cells were incubated at 37 °C for another 2 h. Finally, the absorbance values of the samples were measured at 450 nm by a microplate reader (Spectra Max M2).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Compounds 78 and 79 showed significant inhibitory activity against LPS-induced NO production in RAW 264.7 cells, with IC 50 values of 8.8 and 18.1 μM, respectively, being more potent than the positive control dexamethasone (IC 50 = 22.2 μM). Meanwhile, these dimeric benzophenones were more active than the monomer pleosporone F. 56…”
Section: Naturally Occurring Methylene-bridged Dimersmentioning
confidence: 95%
“…[102] More recently, many researchers have reported natural products as anti-inflammatory agents targeting different inflammatory pathways. [103][104][105][106]…”
Section: Recent Reports On Natural Products As Anti-inflammatory Agentsmentioning
confidence: 99%